1997
DOI: 10.1016/s0092-8674(00)80540-1
|View full text |Cite
|
Sign up to set email alerts
|

Monoallelically Expressed Gene Related to p53 at 1p36, a Region Frequently Deleted in Neuroblastoma and Other Human Cancers

Abstract: We describe a gene encoding p73, a protein that shares considerable homology with the tumor suppressor p53. p73 maps to 1p36, a region frequently deleted in neuroblastoma and other tumors and thought to contain multiple tumor suppressor genes. Our analysis of neuroblastoma cell lines with 1p and p73 loss of heterozygosity failed to detect coding sequence mutations in remaining p73 alleles. However, the demonstration that p73 is monoallelically expressed supports the notion that it is a candidate gene in neurob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

37
1,733
0
18

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,517 publications
(1,788 citation statements)
references
References 52 publications
37
1,733
0
18
Order By: Relevance
“…While p53 was long considered to be unique, recently two p53-related genes were discovered (Kaghad et al, 1997;Osada et al, 1998;Yang et al, 1998). TP73 and TP63 encode proteins with remarkable sequence homology to p53, suggesting that they are also involved in the regulation of cell growth and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While p53 was long considered to be unique, recently two p53-related genes were discovered (Kaghad et al, 1997;Osada et al, 1998;Yang et al, 1998). TP73 and TP63 encode proteins with remarkable sequence homology to p53, suggesting that they are also involved in the regulation of cell growth and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…TP73 and TP63 encode proteins with remarkable sequence homology to p53, suggesting that they are also involved in the regulation of cell growth and apoptosis. Indeed, in experimental systems, p73 showed many p53-like properties: it could bind to p53 DNA binding sites, transactivate p53-responsive genes and induce cell cycle arrest or apoptosis (Jost et al, 1997;Kaghad et al, 1997). However, despite an extensive search tumor-associated mutations of p73 were rarely identified (Stiewe and Pu¨tzer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…First, p73 has substantial structural similarity to p53 in all three domains, (Kaghad et al, 1997; reviewed by Dickman, 1997) and functionally it induces programmed cell death by activating p21 Wa¯/Cipl (Jost et al, 1997). Second, p73 maps to 1p36.33, a region which showed frequent deletions from the maternal chromosome in neuroblastoma and other tumors (Takeda et al, 1994;Versteeg et al, 1995).…”
mentioning
confidence: 99%
“…Second, p73 maps to 1p36.33, a region which showed frequent deletions from the maternal chromosome in neuroblastoma and other tumors (Takeda et al, 1994;Versteeg et al, 1995). Finally, monoallelic expression of p73 is present exclusively in numerous cell lines and normal tissues and individuals tested, as expected of an imprinted gene (Kaghad et al, 1997; reviewed by Oren, 1997). However, no study to date has shown that p73 is imprinted by analysing its expression in human tissues isolated from suitably informative families.…”
mentioning
confidence: 99%
“…Similar to p53, p73 and p63 can form homo-oligomers, bind to canonical p53 DNA-binding sites, modulate the transcription of p53-responsive genes and suppress growth or induce apoptosis when overexpressed in certain human tumors (Jost et al, 1997;Kaghad et al, 1997;Osada et al, 1998;Yang et al, 1998). Each protein also shares significant homology with p53 in its transactivation domain, DNAbinding domain (DBD) and oligomerization domain.…”
Section: Introductionmentioning
confidence: 99%